If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9.74 + -3.31m = 6.43 Solving 9.74 + -3.31m = 6.43 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-9.74' to each side of the equation. 9.74 + -9.74 + -3.31m = 6.43 + -9.74 Combine like terms: 9.74 + -9.74 = 0.00 0.00 + -3.31m = 6.43 + -9.74 -3.31m = 6.43 + -9.74 Combine like terms: 6.43 + -9.74 = -3.31 -3.31m = -3.31 Divide each side by '-3.31'. m = 1 Simplifying m = 1
| -6(8x-9)=7(4-8x)-12+4x | | 9n-16=6n+7 | | 210.00+0.25x=370.00 | | 9.74-3.31=6.43 | | 18-6a=4a-4(q+3) | | 7(3-x)-5(3-2y)-4(9-y)=3(y+5) | | 40+20x=25+45x | | 5x-2(x-2)=7x+4-4x | | z=4x^3+12xy+6y^2 | | 58=6n+10 | | n+2=2-7n | | 10x+20x-6=6(5x+10) | | 2-2x=6x-14 | | 4(2z+12)=8(z-3)+36 | | -6n-4=6-8n | | 8m-10=-66 | | 6(2(y+x))= | | -6n-4=4-8n | | 20x-6=4(5x+4) | | 3=(4-2u)-6u | | 45=5d-21+2d | | 5x+1+5x=13+8x | | 6p=55 | | 2(-3x+7)+4x-3=5-4(2x+9)+1 | | x-4=12+1-x-1 | | 5=4n+15 | | 7x+18x-8=5(5x+4) | | 5m+4(5m-9)=-5(3-5m) | | 4+1+8k-4k=k-1 | | [(X)(x)]-10x=-21 | | 1/12x+3=1/4x-5 | | -8-3w=5w+10+6 |